2002
DOI: 10.1021/jf025932w
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Phenolic Composition and Antioxidant Activity of Virgin Olive Oil during Frying

Abstract: The concentration of hydroxytyrosol (3,4-DHPEA) and its secoiridoid derivatives (3,4-DHPEA-EDA and 3,4-DHPEA-EA) in virgin olive oil decreased rapidly when the oil was repeatedly used for preparing french fries in deep-fat frying operations. At the end of the first frying process (10 min at 180 degrees C), the concentration of the dihydroxyphenol components was reduced to 50-60% of the original value, and after six frying operations only about 10% of the initial components remained. However, tyrosol (p-HPEA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
123
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(139 citation statements)
references
References 34 publications
12
123
2
2
Order By: Relevance
“…The modified method introduced of Brand-Williams et al (1995) has been extensively used (Gomez-Alonso et al 2003;Yepez et al 2002). This suggested the oversimplification of the interpretation by Blois (1958) and that because of the complexity of the reactions that follow the Eq.…”
Section: Original Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified method introduced of Brand-Williams et al (1995) has been extensively used (Gomez-Alonso et al 2003;Yepez et al 2002). This suggested the oversimplification of the interpretation by Blois (1958) and that because of the complexity of the reactions that follow the Eq.…”
Section: Original Methodsmentioning
confidence: 99%
“…The 1 max , used for the absorbance measurements are 515 nm (Gomez-Alonso et al 2003;Lebeau et al 2000), 516 nm (Schwarz et al 2001), 517 nm (Lu and Foo 2000;Zhu et al 2002), 518 nm (Leitao et al 2002) and 520 nm (Kim et al 2002). A reaction time of 30 min was followed by Kim et al (2002).…”
Section: Recommended Methods Of Measurement and Interpretationmentioning
confidence: 99%
“…In general, research has shown that olive oil phenolic compounds are subject to degradation upon the application of heat during cooking (Brenes et al, 2002, Gomez-Alonso et al, 2003. However, oleocanthal has demonstrated to be relatively stable upon heating when the EVOO contains a considerable quantity of this compound initially.…”
Section: Domestic Heat Applicationmentioning
confidence: 99%
“…Fats and oils are largely responsible for the pleasant creamy taste of foods; therefore, its physiological characteristic is important (Belitz et al 2009). Frying causes oil to undergo a wide range of reactions, namely hydrolysis, oxidation, isomerization, and polymerization due to high temperature and absorption of water and oxygen (Go'mez-Alonso et al 2003;Gloria and Aguilera 1998). The deteriorated oil has nutritional and toxicological implication on human health since the toxic substances may accumulate in oil through the food stuff fried in it; final products fried in deteriorated oil possess unpleasant taste, odor and texture (Tena et al 2009).…”
Section: Introductionmentioning
confidence: 99%